Potential Risks of Open Waste Burning at the Household Level: A Case Study of Semarang, Indonesia - Bimastyaji Surya Ramadan; Raden Tina Rosmalina; Syafrudin; Munawir; Hafizhul Khair; Indriyani Rachman; Toru Matsumoto (Aerosol and Air Quality Research)
Abstract Open waste burning (OWB) is a common disposal practice in several countries. However, this activity can serve as a source of particulate matter and black carbon, which possess a greater greenhouse effect potential than CO2. Moreover, particulates can produce chronic health impacts on residents around the burning areas. Therefore, the present study aimed to examine the environmental effects and health risks associated with the open burning of household waste in Semarang, Indonesia. Four steps were followed to answer the research questions: (1) data collection through a random questionnaire survey, transect walk, and field survey; (2) estimation of environmental risk using the IPCC calculation method; (3) multiplication of emission factors to determine black carbon emissions; and (4) estimation of health risks based on chemical speciation bound to particulate matter. Open burning remained the second most common waste disposal practice even after the implementation of waste collection services by the government. Specifically, approximately 240.28 tons of waste is not collected by the environmental agency service every day, and 88.6% of the uncollected waste in the city is openly burned. Plastic burning contributed to the highest emission share among waste components, and annual total emissions due to OWB were estimated at approximately 53,809.66 tons. Although the carcinogenic risk was low, non-cancer disease risk exceeded the standard. Therefore, direct exposure of residents to OWB may pose significant health risks. The present work fills the scientific and knowledge gaps in the OWB studies.